2014
DOI: 10.1371/journal.pone.0101255
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of High-Risk Human Papillomavirus Infections Using Clinician- and Self-Collected Cervical Sampling Methods in Rural Women from Far Western Nepal

Abstract: IntroductionNepal has one of the highest cervical cancer rates in South Asia. Only a few studies in populations from urban areas have investigated type specific distribution of human papillomavirus (HPV) in Nepali women. Data on high-risk HPV (HR-HPV) types are not currently available for rural populations in Nepal. We aimed to assess the distribution of HR- HPV among rural Nepali women while assessing self-collected and clinician-collected cervico-vaginal specimens as sample collection methods for HPV screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 27 publications
5
31
1
Order By: Relevance
“…[16] Nepal Fertility Care Center conducted health camp in Achham District of rural far western which was first study in Nepal to identify high risk HPV (HR-HPV) among rural women and found prevalence rate is 9.6%. [17] …”
Section: American Journal Of Cancer Preventionmentioning
confidence: 99%
“…[16] Nepal Fertility Care Center conducted health camp in Achham District of rural far western which was first study in Nepal to identify high risk HPV (HR-HPV) among rural women and found prevalence rate is 9.6%. [17] …”
Section: American Journal Of Cancer Preventionmentioning
confidence: 99%
“…Over 2100 cases of cervical cancer are reported in Nepal each year, with a case-fatality rate of over 50%. 3 In developing countries, the higher prevalence of cervical cancer is due to ineffective screening programmes. Pap smear is a simple, convenient, cost effective and reliable test for easy screening of cervical lesions.…”
Section: Introductionmentioning
confidence: 99%
“…13 Briefly, health camp auxiliary nurse midwives collected cervical specimens using ThinPrep PreservCyt medium (Hologic/Gen-Probe Inc. San Diego, CA, USA). Cervical specimens were transported to the Hologic/Gen-Probe Inc. laboratory in San Diego for HPV testing.…”
Section: Laboratory Analysismentioning
confidence: 99%
“…13 Briefly, survey questions were translated from English into Nepali, and then back-translated to English for quality control. The local Nepali dialect called Dotyali is sometimes spoken in the district of Achham and does not have a written form, and thus the survey could not be translated into the local Achham dialect.…”
Section: Demographic and Health Risk Surveymentioning
confidence: 99%
See 1 more Smart Citation